Database and expert systems applications. 28th International Conference, DEXA 2017, Lyon, France, August 28-31, 2017, Proceedings /: 28th International Conference, DEXA 2017, Lyon, France, August 28-31, 2017, Proceedings. Part II : ([2017]) - Unknown
No abstract available